Early Identification of Potential Increases in Construction Costs Based on SAP S/4 HANA - Gunawan, Ratih Yuliani; Girsang, Hamonangan; Djawu, Patricia Kanicia (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
The construction industry plays a strategic role in developing infrastructure and facilities. However, issues such as cost overruns often lead to losses in the construction project implementation. This issue has been highlighted recently, especially in state-owned construction service companies. Rapid evaluation of cost control is crucial to mitigate potential project cost increases. This is because a cost overrun can potentially harm the company. Therefore, cost control in construction projects becomes a very important aspect and needs to be managed effectively. Currently, one of the software programs widely used in company cost management is the SAP S/4 HANA program, an Enterprise Resource Planning (ERP) application. This research aims to identify the potential of construction cost overruns. Through the data analysis conducted, this research includes analysis of cost management in construction projects, project implementation budgets, work breakdown structure (WBS), and cost breakdown structure (CBS). It presents solutions for potential cost overruns early using SAP S/4 HANA in the University XYZ building project. The research was conducted using a literature study and a quantitative analysis method—data collection from interviews and analysis, as well as conclusions. Data processing using the SAP S/4 HANA program provides advantages in providing real-time information about the project budget conditions and enables effective and efficient decision-making. The research findings indicate that Top management support, Vendor support, User Training, and SAP S/4 HANA’s report can influence the successful implementation of SAP S/4 HANA in early detection. The analysis of the final project costs based on the SAP S/4 HANA Project System module in the University XYZ Lecture Building Project indicates a potential construction cost increase.